(untitled) (Research, Society and Development, 2023)
Reactive oxygen species (ROS), when in excess, cause damage to biomolecules (DNA, lipids, carbohydrates, and proteins), which are related to several pathologies. There is a growing study of substances that act to inhibit or reduce the action of these ROS. Chalcones are aromatic ketones with a naturally occurring and easily synthesized α,β-unsaturated system. In this work, we investigated the in vitro protective action of a new class of chalcones functionalized by the thiobarbituric acid reactive substances (TBARS) assay. The most promising molecule (Chalcone E) was submitted to the DPPH radical scavenging assay, and the MTT cell viability test evaluated its cytotoxicity. In addition, Chalcone E reduced lipid peroxidation, with maximum inhibition values of 73.05% for the brain, 81.42% for the liver, and 87.23% for the kidney, demonstrating a potential antioxidant effect. Still, the DPPH test did not observe this effect, suggesting further investigation of this molecule.